Pesticide resistance in arthropods: Ecology matters too - Bras, Audrey; Roy, Amit; Heckel, David G; Anderson, Peter; Karlsson Green, Kristina (Ecology letters, 2022)
Pesticide resistance development is an example of rapid contemporary evolution that poses immense challenges for agriculture. It typically evolves due to the strong directional selection that pesticide treatments exert on herbivorous arthropods. However, recent research suggests that some species are more prone to evolve pesticide resistance than others due to their evolutionary history and standing genetic variation. Generalist species might develop pesticide resistance especially rapidly due to pre-adaptation to handle a wide array of plant allelochemicals. Moreover, research has shown that adaptation to novel host plants could lead to increased pesticide resistance. Exploring such cross-resistance between host plant range evolution and pesticide resistance development from an ecological perspective is needed to understand its causes and consequences better. Much research has, however, been devoted to the molecular mechanisms underlying pesticide resistance while both the ecological contexts that could facilitate resistance evolution and the ecological consequences of cross-resistance have been under-studied. Here, we take an eco-evolutionary approach and discuss circumstances that may facilitate cross-resistance in arthropods and the consequences cross-resistance may have for plant-arthropod interactions in both target and non-target species and species interactions. Furthermore, we suggest future research avenues and practical implications of an increased ecological understanding of pesticide resistance evolution.
Keywords: Plants; Arthropods; pesticidy; Biological Evolution; rezistence k insekticidům; zvířata; diet breadth; integrated pest management; býložravci; Pesticides; Herbivory; členovci; agroecosystem; co-evolution; Insecticide Resistance; insecticide resistance; biologická evoluce; plant-insect interaction; Animals; rostliny